Oral microbial biofilm stimulation of epithelial cell responses - Peyyala, Rebecca (2012)
Oral bacterial biofilms trigger chronic inflammatory responses in the host that can result in the tissue destructive events of periodontitis. However, the characteristics of the capacity of specific host cell types to respond to these biofilms remain ill-defined. This report describes the use of a novel model of bacterial biofilms to stimulate oral epithelial cells and profile select cytokines and chemokines that contribute to the local inflammatory environment in the periodontium. Monoinfection biofilms were developed with Streptococcus sanguinis, Streptococcus oralis, Streptococcus gordonii, Actinomyces naeslundii, Fusobacterium nucleatum, and Porphyromonas gingivalis on rigid gas-permeable contact lenses. Biofilms, as well as planktonic cultures of these same bacterial species, were incubated under anaerobic conditions with a human oral epithelial cell line, OKF4, for up to 24 h. Gro-1α, IL1α, IL-6, IL-8, TGFα, Fractalkine, MIP-1α, and IP-10 were shown to be produced in response to a range of the planktonic or biofilm forms of these species. P. gingivalis biofilms significantly inhibited the production of all of these cytokines and chemokines, except MIP-1α. Generally, the biofilms of all species inhibited Gro-1α, TGFα, and Fractalkine production, while F. nucleatum biofilms stimulated significant increases in IL-1α, IL-6, IL-8, and IP-10. A. naeslundii biofilms induced elevated levels of IL-6, IL-8 and IP-10. The oral streptococcal species in biofilms or planktonic forms were poor stimulants for any of these mediators from the epithelial cells. The results of these studies demonstrate that oral bacteria in biofilms elicit a substantially different profile of responses compared to planktonic bacteria of the same species. Moreover, certain oral species are highly stimulatory when in biofilms and interact with host cell receptors to trigger pathways of responses that appear quite divergent from individual bacteria.